סגפנות בקרב היהודים הסופים במצרים: תוך התייחסות מיוחדת לתורתו של ר' אברהם בן הרמב"ם ור' דוד השני בן הרמב"ם - פנטון, ינון יוסף (מחשבת ישראל, 2021)
In order to situate the theory and practice of asceticism among the Judeo Sufis of Egypt within the larger context of medieval Jewish thought, and to highlight the special importance they lent to asceticism, the present article gives a brief survey of the general approaches to the discipline of zuhd among medieval Judeo-Arabic thinkers from Sa‘adya to Maimonides. Most medieval writers on asceticism from within this tradition advocated a moderate form of renunciation. This article argues for a subtler distinction within the Jewish tradition by looking more closely at one cultural and chronological sphere: the Judeo-Sufis of Medieval Egypt. There thus follows an in-depth synopsis of asceticism presented in the works of two of Maimonides’ descendants, his son R. Abraham Maimuni (1186-1237) and R. David ben Joshua Maimuni (14th century), who were leaders of the Egyptian Jewish pietist movement. It introduces the reader to the main elements of asceticism in these two thinkers’ thought, notably making use of heretofore unpublished manuscripts of David’s works. The author argues that Abraham and David propound a more acute expression of asceticism, not merely as a “therapeutic” means towards attaining a temperate ethical disposition, but as an ideal, and, in the case of R. David, an indispensable stage in the Path towards gnosis. The article claims that this new emphasis may be explained, on the one hand, by the impact of the Sufi environment predominant in 13th-15th century Egypt on Abraham and David’s approach, and, on the other, by their ideal of spiritual preparation in anticipation of the renewal of prophecy and the ensuing redemption. On the second point, the author also suggests that some of the pietists’ ascetic practices may have been adopted by early Qabbalists in the East from a similar perspective.